Three phase inverter control using DSP controller for dynamic voltage restorer (DVR) application - Omar, Rosli; Rahim, Nasrudin (Academic Journals, 2011)
This paper discusses the control technique improvement of a three-phase inverter using directquadrature- zero (d-q-0) controller based on DSP TMS320F2812 for dynamic voltage restorer (DVR) applications. The output of the inverter is then connected to a voltage grid via a second order filter and injection transformer. The control algorithms are developed using TMS320F 2812 DSP. The proposed technique achieves voltage regulation with low total harmonics distortion (THD) for both voltage and current. This paper also highlights a series of discussion, analysis and studies performed on the proposed control technique, including L-C filter design issue and the concept of DVR in the distribution system. An analysis and experimental results validate the effectiveness of the DSP controller in mitigating voltage sags and harmonics issues in the distribution system